Morphological , Anatomical and Chemical Studies of Salvia Rosmarinus Spenn. Growing in Al- Marj (Libya) - Mahmoud, Wafa Ahmed (Al-Mukhtar Journal of Sciences, 2023)
Salvia rosmarinus Spenn (synonym: Rosmarinus officinalis L.) is economically and medically important and grows naturally in Al-Marj (Libya). Macro, micro morphological and chemical characteristics were studied. Leaf venation, leaf anatomy and chemical compounds of essential oils were carried out according to traditional methods. The objective of the present study is to provide detailed description of the characteristics of this species. Morphological charactersistics of leaves, calyx, corolla, stamens are useful for sectional and specific delimitations in Salvia. The leaf architecture characters of primary, secondary, tertiary and quaternary veins are good diagnostic markers for the identification and classification of species. Anatomical characters such as glandular and non- glandular trichomes , mesophyll structure, presence of hypodermis and structure of vascular bundles have been found to have taxonomic value. Cineol (32.38%) is main component of essential oil, followed by Camphor, β-pinene, borneol, Caryophyllene, α-terpineol and α-pinene. Chemical data in essential oils carried taxonomic value of Salvia species.